Castor oil–citric acid copolyester for tissue augmentation1. (17th June 2014) - Ickowicz, Diana E.; Haim‐Zada, Moran; Abbas, Randa; Touitou, Dan; Nyska, Abraham; Golovanevski, Ludmila; Weiniger, Carolyn F.; Katzhendler, Jeoshua; Domb, Abraham J.; Lendlein, Andreas; Behl, Marc
<x xml:space="preserve">Abstract</x> Biodegrable polyesters derived from hydroxy acids have a broad clinical use. The aim of the study was to synthesize polymer compositions based on citric acid and castor oil for use as soft tissue augmentation. Two polymers were synthesized, a branched viscous polyester with a monomer ratio of 93.5:6.5 w/w and an apparent molecular weight of 11, 000 Da and a crosslinked semisolid polymer with a monomer ratio of 92.5:7.5 w/w. The branched polymer lost less than 10% of its weight during a 30‐day degradation study. In vivo biocompatibility study in rats showed 20% formulation weight loss 9 months post‐subcutaneous administration. These results were in accordance with the in vitro hydrolytic degradation of the polymer. The in vivo study revealed good tolerability of the copolymer. Copyright © 2014 John Wiley & Sons, Ltd.